Evaluación del sedimento urinario a los 30, 60, 120 y 360 minutos en pacientes que acuden al Hospital Regional Clínico-Quirúrgico “Daniel Alcides Carrión”, 2022 - De la Cruz Curazzi, Luz Milagros (2022)
The aim of this research was to describe the microscopic analysis of urinary sediment, evaluated at 30, 60, 120 and 360 min of emergency patients of the Hospital Regional Clínico-Quirúrgico "Daniel Alcides Carrión" in the year 2021. The study was descriptive and comparative, with a non-experimental design; the general method was scientific, and the specific method was descriptive. The data for the research were obtained from the records of the hospital under study, for which a total of 120 patients were evaluated in five samples for the evaluation time of 30, 60, 120 and 360 minutes, in addition to the baseline evaluation. The results of the research show that there is indeed a change in the elements of the urinary sediment, mainly on red blood cells and with a lesser effect on epithelial cells and leukocytes.